Menyiapkan Guru Abad 21: Pelatihan Desain Pembelajaran Bahasa Indonesia Berbasis Literasi Digital bagi Mahasiswa PGMI di UIN Sayyid Ali Rahmatullah Tulungagung - Rohmah Ivantri (LPPI UMN AL WASHLIYAH, 2025)
Improving the quality of education in Indonesia greatly depends on teachers' competencies in designing and implementing effective and contextual learning. This study focuses on developing instructional design skills in teaching Indonesian Language using digital literacy among students of the Primary School Teacher Education Program (PGMI) at UIN Sayyid Ali Rahmatullah Tulungagung. Preliminary findings show that most PGMI students still rely on conventional methods that are less responsive to technological advancements and 21st-century literacy demands. To address this, a training program was conducted involving the development of technology-based teaching modules, collaborative workshops, and microteaching simulations integrating digital media. The training aimed to enhance students’ abilities to design relevant and innovative learning experiences, preparing them as competent future teachers in the digital era. The training method adopted a hands-on practice-based approach using the Asset-Based Community Development (ABCD) model. Evaluation was carried out through pre-tests, post-tests, questionnaires, and open-ended interviews to assess skill improvement and student perceptions. The results indicated a significant increase in students' ability to develop digital literacy-based teaching modules, along with improved confidence and creativity in designing adaptive 21st-century learning. These findings support the constructivist approach and the TPACK model, which integrates technology, pedagogy, and content in the learning process. This training not only enhanced students’ technical skills but also fostered their professionalism as reflective and innovative future educators. The study is expected to contribute to the development of teacher competencies better equipped to face the challenges of digital transformation in primary education.